A Sustainable Framework of Micro Entrepreneurship Aiming Towards Self-Sufficiency for Lower Income Groups - Mushtaq, Saleem; Shameem, Beenish (AMC Indian Journal of Entrepreneurship, 2020)
The purpose of this paper was to provide a strong framework which will provide a roadmap for starting home-based business for the rural population of Jammu and Kashmir. There are a host of factors that contribute to the financial meagerness of people. Some of them are not having enough education, lack of awareness, eagerness to migrate in search of job opportunities, and leave their homes not realizing the potential of farming, poultry, and many more. In this investigative study, an attempt was made to offer a model to the people so that rural population can start their own business without any major investments and without possessing any professional qualifications. The only prerequisites of starting a business here are owning and rearing chicken with a minimum count of 8 to 10, which is usually common for the people living in rural Jammu & Kashmir in particular, and India in general.